Mumbai hors cadre Une géographie de l'art contemporain en Inde - Ithurbide, Christine (De l'Orient à l'Occident, 2022)
Indian contemporary art has become fully integrated into global institutional and commercial dynamics in the decades following India's economic liberalization in the 1990s. Bombay, which has been a commercial capital and cultural crossroads in Asia since the end of the nineteenth century, has become the main metropolis for the Indian contemporary art market. Through this industry, which is more discreet than Bollywood but just as globalized, this book invites us to discover - or rediscover - Bombay/Mumbai. Taking the art gallery and museum district in the south of the city as her starting point, the author draws us into a complex geography of contemporary art that highlights multiple networks of workshops and invisible workers, installed in the industrial districts where the artworks are made. Based on ten years of fieldwork in India, this research opens up a critical analysis of the cultural metropolises of the South, paying attention to the spaces and actors outside the framework, as well as to the power relations linked to local and global socioeconomic contexts.